A primary hydrogen-deuterium isotope effect observed at the single-molecule level. - Lu, S; Li, W; Rotem, D; Mikhailova, E; Bayley, H (2010)
The covalent chemistry of reactants tethered within a single protein pore can be monitored by observing the time-dependence of ionic current flow through the pore, which responds to bond making and breaking in individual reactant molecules. Here we use this 'nanoreactor' approach to examine the reaction of a quinone with a thiol to form a substituted hydroquinone by reductive 1,4-Michael addition. Remarkably, a primary hydrogen-deuterium isotope effect is readily detected at the single-molecule level during prototropic rearrangement of an initial adduct. The observation of individual reaction intermediates allows the measurement of an isotope effect whether or not the step involved is rate limiting, which would not be the case in an ensemble measurement.